Pathology of the salivary glands - Batsakis, John G.; Sylvest, Vernon, 1939- (Chicago : American Society of Clinical Pathologists, 1977)
(Critical) This program discusses the epidemiology, pathogenesis, treatment, prognosis, gross morphology and histomorphology of salivary gland lesions. This presentation is generally well done and accurate and is recommended for oral pathology, pathology and nursing students
Dental : graduate; continuing education. Medical: graduate; continuing education. Specialty: pathology, oral
Keywords: Salivary Gland Diseases -- slides